Social wasps (Vespidae: Polistinae) of Minas Gerais, Brazil: richness and distribution - Diogo Silva Vilela; Júlio César Moreira Dobizc; Luís Cláudio Paterno Silveira; Marcos Magalhães de Souza (Revista Chilena de Entomología)
Minas Gerais state, Brazil, is home to significant biological diversity, including social wasps (Vespidae: Polistinae). However, they have suffered substantial losses of their original cover due to anthropogenic actions, which justifies carrying out inventory studies. Therefore, this study aims to analyze the species richness and distribution of social wasps in Minas Gerais and add information to the municipality of Luminárias, southern Minas Gerais. There are inventories in 32 locations in Minas Gerais, inside and outside Conservation Units (CUs), with a higher concentration in the Atlantic Forest. In total, 118 social wasp species are recorded in the state and 74 are considered rare, i.e. occurring in less than 20% of the localities. The Caatinga, along with the protected areas in the Cerrado and the Atlantic Forest in the eastern and northeastern parts of the state, is under-sampled. Luminárias, despite not being located in a UC, has a considerable richness of rare species, two of which have only been previously recorded in Conservation Units. This allows us to infer that this municipality is home to a relevant vespid fauna for the state, corroborating other studies that suggest the creation of a UC for the region.